2011
DOI: 10.1093/chrsci/49.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa Extract as a Potent Antioxidant for Petrochemical-Induced Oxidative Stress

Abstract: Various beneficial properties has been attributed to Nigella sativa, including its antioxidant potential. Previously, it was reported that supercritical fluid extraction (SFE) could be used to obtain N. sativa extract rich in antioxidants. In the present study, N. sativa extracts prepared using the previously optimized SFE as well as the traditional Soxhlet extraction approaches were analyzed for various known antioxidants. N. sativa extracts were found to prevent protein carbonyl formation as well as depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 24 publications
3
56
0
Order By: Relevance
“…The seeds contain alkaloids and glycoside flavonols such as quercetin, kaempferol, and quercetin-3 [32]. Recently, clinical and animal studies have shown that an extract of NS has many therapeutic effects, including antiproliferative, anti-inflammatory, antitumor, anticancer, multiple myeloma, antibacterial, estrogenic, and antioxidant activity [32,33,34,35,36,37,38,39]. Experimental studies have also revealed that thymoquinone has protective effects against I/R injury in the intestine [40], liver [41], kidney [42], and testicular torsion [43].…”
Section: Introductionmentioning
confidence: 99%
“…The seeds contain alkaloids and glycoside flavonols such as quercetin, kaempferol, and quercetin-3 [32]. Recently, clinical and animal studies have shown that an extract of NS has many therapeutic effects, including antiproliferative, anti-inflammatory, antitumor, anticancer, multiple myeloma, antibacterial, estrogenic, and antioxidant activity [32,33,34,35,36,37,38,39]. Experimental studies have also revealed that thymoquinone has protective effects against I/R injury in the intestine [40], liver [41], kidney [42], and testicular torsion [43].…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the decrease in GPX activity might be due to partial inhibition of lipid peroxidation and the consequent decrease in the reduction of H 2 O 2 . TQ has been proven to possess a potent antioxidant effect in terms of scavenging properties on free radicals such as superoxide anion [8,9,10,15,38]. A number of studies have demonstrated beneficial effects of various antioxidants and their free radical scavenging property in prostatitis [38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The seeds of N. sativa have long been used in the Middle and Far East as a traditional medicine for a wide range of illnesses. TQ is a bioflavonoid with antioxidant, anti-inflammatory, neuroprotective, antiallergenic, antiviral, antidiabetic, and anticarcinogenic properties [8,9,10]. TQ may have a protective effect against inflammation, membrane lipid peroxidation, and infection-induced prostate toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have revealed the benefi ts of extraction used in a spectrum from infectious diseases to cardiovascular system diseases (8,9). The studies relevant to pharmacological properties of TQ have suggested that antioxidant and antiinfl ammatory effects can be effective but research on the subject has not been suffi ciently illuminated (10). In this study, oxidative and anti-infl ammatory activities of TQ were investigated under infl ammatory condition by intraperitoneal administration of TQ.…”
Section: Introductionmentioning
confidence: 97%